The Internet Economy - Regulatory Challenges and Practices - Koske, Isabell (OECD Economics Department Working Papers, 2014)
The Internet has become an integral part of the everyday life of households, firms and governments. Its proper functioning over the long run is therefore crucial for economic growth and people's wellbeing more generally. The success of the Internet depends on its openness and the confidence of users. Designing policies that protect society while allowing for Internet's great economic potential to be fulfilled, is a difficult task. This paper investigates this challenge and takes stock of existing regulations in OECD and selected non-OECD countries in specific areas related to the digital economy. It finds that despite the regulatory difficulties, the Internet is far from being a "regulation-free" space as there are various industry standards, co-regulatory agreements between industry and the government, and in some cases also state regulation. Most of them aim at protecting personal data and consumers more generally. In many cases generally applicable laws and regulations exist that address privacy, security and consumer protection issues both in the traditional and the digital economy